O'Reilly software architecture conference 2015 (O'Reilly Media, 2015)
"You need to build considerable sills, knowledge, and judgment to become a software architect -- and learning doesn't stop once you have a title. Quick-paced and practical, O'Reilly's inaugural Software Architecture Conference in Boston provided the professional training that veteran and aspiring software architects, engineers, and senior developers need to stay on top of this fast-moving discipline. And now you can access the entire conference from the comfort of your office or home. This complete video compilation includes every keynote, session, workshop, training, and event. Download these videos or stream them through our HD player, and stay current with emerging technologies, hone your leadership skills, and support the success of your business. This in-depth professional training covers software architecture fundamentals, real-world case studies, and the latest trends in technologies, frameworks, and techniques."--Resource description page.